Application of Wolfram Mathematica program to the determination of the main parameters of white dwarf stars - Boshkayev, K.A.; Zhami, B.A.; Kalymova, Zh.A. (Recent Contributions to Physics, 2018)
In this work the application methodology of Wolfram Mathematica program is considered in order to calculate the basic characteristics of white dwarf stars. The main quantities of static cold (zero temperature) white dwarfs such as the mass, radius, and density have been determined within the framework of classical physics. To determine these parameters the system, consisting of the differential equations such as the Newtonian equation of hydrostatic equilibrium, the mass balance equation and the equation of state of the degenerate electron gas, has been solved. These equations cannot be solved analytically, and therefore a special code has been written for solving the equations numerically. In terms of the numerical solutions the main parameters of white dwarfs have been computed and the mass-radius, mass-central density, radius-central density relations have been constructed. All calculations are shown in detail with methodological instructions as an example. The work is dedicated to the undergraduate, graduate, PhD students and young experts of higher educational institutions of specialties physics, physics and astronomy.